A critical discourse analysis of a rural health promotion project: Exploring insights for evaluation - Catherine E. Sanders; Alexa J. Lamm; Abigail Borron; Jori Hall; Maria Navarro; James C. Anderson (Journal of Rural Studies, 2026)

Diversity in a shrinking alpine world: how does the expansion of krummholz ecotones alter microclimates and alpine plant diversity? - Alexa A. C. MacDonald; Scott E. Nielsen (Alpine Botany, 2026)

The impact of mild hypohydration and sex on the cardiovascular responses to progressive lower-body negative pressure - Megan Hunt; Jenna C. McCrone; Christopher Pignanelli; Monica M. Grigore; Katrin Turetskiy; Gavin C. Lydiate; Alexa A. Robertson; Regan E. J. Parris; Ella M. Bisset-Cavallin; Connor Wideman; Philip J. Millar; Jamie F. Burr; et al. (European Journal of Applied Physiology, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

The nucleus accumbens to ventral pallidum pathway regulates social play behavior via sex-specific mechanisms in juvenile rats - Jessica D. A. Lee; Daniela N. Anderson; Isabella C. Orsucci; Samantha M. Bowden; Alexa H. Veenema (Brain Structure and Function, 2026)
Social play behavior is a rewarding behavior predominantly displayed by juveniles of various mammalian species, including humans and rats. Although the mesolimbic reward system is involved in the regulation of social play, how brain regions in this system interact to regulate social play behavior is unknown. Here, we determined the involvement of the ventral pallidum (VP) as well as inputs from the nucleus accumbens (NAc) to the VP in the regulation of social play in male and female juvenile rats. We show that acute pharmacological inactivation of the VP, via microinfusion of the GABA-A receptor agonist muscimol, decreased social play behaviors in both sexes. Next, using Gad1-iCre rats, we show that chemogenetic stimulation of NAc GABA terminals in the VP decreased VP neuronal activation and decreased social play behaviors in both sexes. These findings together indicate that reduced inhibitory NAc input to the VP permits activation of the VP which facilitates the expression of social play behaviors. Lastly, we show that the equal expression of social play behavior in males and females is associated with a male-specific decrease in fos activation of NAc shell neurons projecting to the VP. This sex-specific change in NAc shell activation following social play exposure eliminated a baseline sex difference in NAc shell activation. In conclusion, these findings may support a model in which the sex-specific modulation of NAc shell inhibitory input to the VP facilitates activation of the VP that is necessary for the typical and equal expression of social play behavior in male and female juvenile rats.

Assessment of the Orbit® subretinal delivery system (Orbit® SDS device) and prototypes in adult and juvenile canine eyes - Jennifer C. Kwok; Alexa P. Gray; Yu Sato; Svetlana Savina; Natalia Dolgova; Raghavi Sudharsan; Sanford L. Boye; Shannon E. Boye; Sam Reichenbacker; Tom Meyer; Kirsten Stoner Cummiskey; William A. Beltran (Drug Delivery and Translational Research, 2026)
This study aimed to assess the applicability of the Orbit ® Subretinal Delivery System [Orbit ® SDS, 2nd Generation, clinical-grade device] and prototypes for subretinal injection (SRI) in dogs of different ages. Following ex vivo and in vivo testing of the clinical grade Orbit ® SDS in 7 adult canine eyes, 8 normal dogs (13 eyes; age range: 10–72 weeks) were injected with an AAV2/5-CBA-tdTomato-WPRE vector using different Orbit ® SDS prototype devices. Dogs underwent non-invasive fundus photography regularly post-injection (PI). Retinal imaging including optical coherence tomography (OCT) angiography (OCTA) and en face null OCT was performed in most dogs at 5- and 9-weeks PI. Following termination, eyes were examined histologically. Ex vivo and in vivo SRI could be performed in 7 adult eyes including in that of a dog with end stage retinal degeneration. SRI of AAV2/5-CBA-tdTomato-WPRE was also successful in all 13 eyes including those of juvenile animals, yet this frequently required multiple attempts and/or using custom-modified devices that were adjusted to the smaller curvature of the ocular globes. Localized tdTomato expression was found in 11/13 eyes along the cannula path in the suprachoroidal space (SCS) in the sclera and choroid. Clinical and cellular signs of inflammation were seen in 7/13 eyes. The Orbit ® SDS device allows for controlled subretinal injections via a posterior approach in adult and juvenile dogs. There was variable vector reflux from the subretinal bleb and/or leakage from the device into the SCS. A cellular immune reaction to the AAV capsid/transgene may have contributed to retinal and choroidal inflammation.

The COSPAR international space weather action teams (ISWAT) initiative: a driving force for the COSPAR space weather roadmap - Maria M. Kuznetsova; Mario M. Bisi; Hermann J. Opgenoorth; Martin A. Reiss; M. Leila Mays; Lucilla Alfonsi; C. Nick Arge; David Barnes; Anna Belehaki; Thomas E. Berger; Amanda Brecht; Sean Bruinsma; et al. (Advances in Space Research, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

A Review of American Lobster ( Homarus americanus ) Research Since 2000 - Jason S. Goldstein; Benjamin C. Gutzler; Andrew S. Kough; Joshua T. Carloni; Alexa M. Dayton; Carla M. Guenther; Steven H. Jury; Winsor H. Watson (Reviews in Fisheries Science & Aquaculture, 2026)

Longitudinal effects of cerebrovascular reactivity and cerebral pulsatility in cognitively intact older adults with APOE4: links with cognition - Zacharie Potvin-Jutras; Pierre-Luc Tremblay; Hanieh Mohammadi; Sylvia Villeneuve; R. Nathan Spreng; Claudine J. Gauthier; Sylvia Villeneuve; Judes Poirier; John C.S. Breitner; Jennifer Tremblay-Mercier; Jordana Remz; Jean-Michel Raoult; et al. (GeroScience, 2025)

Deep-sea ecosystems of the North Atlantic Ocean: discovery, status, function and future challenges - A. Louise Allcock; Diva J. Amon; Amelia E.H. Bridges; Ana Colaço; Elva Escobar-Briones; Ana Hilário; Kerry L. Howell; Nélia C. Mestre; Frank E. Muller-Karger; Imants G. Priede; Paul V.R. Snelgrove; Kathleen Sullivan Sealey; et al. (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Extreme events drive rapid and dynamic range fluctuations - Lydia G. Soifer; Julie L. Lockwood; Jonas J. Lembrechts; Laura H. Antão; David H. Klinges; Rebecca A. Senior; Natalie C. Ban; Birgitta Evengard; Belen Fadrique; Sophie Falkeis; Alexa L. Fredston; Rob Guralnick; et al. (Trends in Ecology & Evolution, 2025)

Reimagining species on the move across space and time - Alexa L. Fredston; Morgan W. Tingley; Montague H.C. Neate-Clegg; Luke J. Evans; Laura H. Antão; Natalie C. Ban; I-Ching Chen; Yi-Wen Chen; Lise Comte; David P. Edwards; Birgitta Evengard; Belen Fadrique; et al. (Trends in Ecology & Evolution, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Natural area visitors’ willingness to pay for amphibian conservation in a global biodiversity hotspot - Kevin Cavasos; Ram K. Adhikari; Neelam C. Poudyal; Alexa R. Warwick; Matthew J. Gray (Journal for Nature Conservation, 2023)

Snapshot of the pollution-driven metabolic and microbiota changes in Carassius gibelio from Bucharest leisure lakes - Ionela C. Voinea; Cristina F. Alistar; Alina Banciu; Roua G. Popescu; Sorina N. Voicu; Mihai Nita-Lazar; Gabriela Geanina Vasile; Stefania Gheorghe; Alexa-Maria Croitoru; Georgiana Dolete; Dan Eduard Mihaiescu; Anton Ficai; et al. (Science of The Total Environment, 2023)

Qualitative Exploration of Cultural Influence on a Rural Health-Promotion Initiative - Nekeisha L. Randall; Catherine E. Sanders; Alexa J. Lamm; Alison C. Berg (Journal of Nutrition Education and Behavior, 2023)

Sex-specific relationships between obesity, physical activity, and gray and white matter volume in cognitively unimpaired older adults - Brittany Intzandt; Safa Sanami; Julia Huck; Anne Labonté; Alexa Pichet Binette; Axel Mathieu; Cynthia Picard; Doris Dea; Claudio Cuello; Alan Evans; Christine Tardif; Gerhard Mulhaup; et al. (GeroScience, 2023)

Emerging harmful algal blooms caused by distinct seasonal assemblages of a toxic diatom - Alexa R. Sterling; Riley D. Kirk; Matthew J. Bertin; Tatiana A. Rynearson; David G. Borkman; Marissa C. Caponi; Jessica Carney; Katherine A. Hubbard; Meagan A. King; Lucie Maranda; Emily J. McDermith; Nina R. Santos; et al. (Limnology and Oceanography, 2022)
Diatoms in the Pseudo‐nitzschia genus produce the neurotoxin domoic acid. Domoic acid bioaccumulates in shellfish, causing illness in humans and marine animals upon ingestion. In 2017, high domoic acid levels in shellfish meat closed shellfish harvest in Narragansett Bay, Rhode Island for the first and only time in history, although abundant Pseudo‐nitzschia have been observed for over 60 years . To investigate whether an environmental factor altered endemic Pseudo‐nitzschia physiology or new domoic acid‐producing strain(s) were introduced to Narragansett Bay, we conducted weekly sampling from 2017 to 2019 and compared closure samples. Plankton‐associated domoic acid was quantified by LC‐MS/MS and Pseudo‐nitzschia spp. were identified using a taxonomically improved high‐throughput rDNA sequencing approach. Comparison with environmental data revealed a detailed understanding of domoic acid dynamics and seasonal multi‐species assemblages. Plankton‐associated domoic acid was low throughout 2017–2019, but recurred in fall and early summer maxima. Fall domoic acid maxima contained known toxic species as well as a novel Pseudo‐nitzschia genotype. Summer domoic acid maxima included fewer species but also known toxin producers . Most 2017 closure samples contained the particularly concerning toxic species, P. australis , which also appeared infrequently during 2017–2019. Recurring Pseudo‐nitzschia assemblages were driven by seasonal temperature changes, and plankton‐associated domoic acid correlated with low dissolved inorganic nitrogen. Thus, the Narragansett Bay closures were likely caused by both resident assemblages that become toxic depending on nutrient status as well as the episodic introductions of toxic species from oceanographic and climatic shifts.

Recommendations for quantifying and reducing uncertainty in climate projections of species distributions - Stephanie Brodie; James A. Smith; Barbara A. Muhling; Lewis A. K. Barnett; Gemma Carroll; Paul Fiedler; Steven J. Bograd; Elliott L. Hazen; Michael G. Jacox; Kelly S. Andrews; Cheryl L. Barnes; Lisa G. Crozier; et al. (Global Change Biology, 2022)
Projecting the future distributions of commercially and ecologically important species has become a critical approach for ecosystem managers to strategically anticipate change, but large uncertainties in projections limit climate adaptation planning. Although distribution projections are primarily used to understand the scope of potential change—rather than accurately predict specific outcomes—it is nonetheless essential to understand where and why projections can give implausible results and to identify which processes contribute to uncertainty. Here, we use a series of simulated species distributions, an ensemble of 252 species distribution models, and an ensemble of three regional ocean climate projections, to isolate the influences of uncertainty from earth system model spread and from ecological modeling. The simulations encompass marine species with different functional traits and ecological preferences to more broadly address resource manager and fishery stakeholder needs, and provide a simulated true state with which to evaluate projections. We present our results relative to the degree of environmental extrapolation from historical conditions, which helps facilitate interpretation by ecological modelers working in diverse systems. We found uncertainty associated with species distribution models can exceed uncertainty generated from diverging earth system models (up to 70% of total uncertainty by 2100), and that this result was consistent across species traits. Species distribution model uncertainty increased through time and was primarily related to the degree to which models extrapolated into novel environmental conditions but moderated by how well models captured the underlying dynamics driving species distributions. The predictive power of simulated species distribution models remained relatively high in the first 30 years of projections, in alignment with the time period in which stakeholders make strategic decisions based on climate information. By understanding sources of uncertainty, and how they change at different forecast horizons, we provide recommendations for projecting species distribution models under global climate change.

Correction to: Solvent Effects on Skin Penetration and Spatial Distribution of the Hydrophilic Nitroxide Spin Probe PCA Investigated by EPR - Pin Dong; Christian Teutloff; Jürgen Lademann; Alexa Patzelt; Monika Schäfer-Korting; Martina C. Meinke (Cell Biochemistry and Biophysics, 2022)

IL-2/IL-2R Antibody Complex Enhances Treg-Induced Neuroprotection by Dampening TNF-α Inflammation in an In Vitro Stroke Model - Mia C. Borlongan; Chase Kingsbury; Felipe Esparza Salazar; Alma R. Lezama Toledo; German Rivera Monroy; Nadia Sadanandan; Blaise Cozene; Bella Gonzales-Portillo; Madeline Saft; Zhen-Jie Wang; Alexa Moscatello; Jea Y. Lee (NeuroMolecular Medicine, 2021)
The present in vitro study showed that IL-2/IL-2R antibody complex facilitates Treg-induced neuroprotection in the oxygen glucose deprivation/reoxygenation (OGD/R) model of stroke. First, we examined the role of IL-2/IL-2R-treated Tregs in OGD/R-exposed rat primary cortical cells (PCCs), which represent the cell type of the ischemic gray matter in the stroke brain. Here, OGD/R induced cell death, which was attenuated by Tregs and more robustly by IL-2/IL-2R-treated Tregs, but not by IL-2/IL-2R treatment alone. Second, we next assessed IL-2/IL-2R effects in OGD/R-exposed human oligodendrocyte progenitor cells (OPCs), which correspond to the white matter injury after stroke. Results revealed that a similar pattern neuroprotection as seen in the gray matter, in that OGD/R triggered cell death, which was ameliorated by Tregs and more effectively by IL-2/IL-2R-treated Tregs, but IL-2/IL-2R treatment alone was not therapeutic. Third, as we begin to understand the mechanism underlying IL-2/IL-2R engagement of Tregs, we investigated the inflammatory response in OGD/R-exposed human neural progenitor cells (NPCs), which recapitulate both ischemic gray and white matter damage in stroke. Similar to PCCs and OPCs, OGD/R produced cell death and was blocked by Tregs and more efficiently by IL-2/IL-2R-treated Tregs, whereas IL-2/IL-2R treatment alone did not alter the ischemic insult. Moreover, the inflammatory marker, TNF-α, was upregulated after OGD/R, dampened by both Tregs and more efficiently by IL-2/IL-2R-treated Tregs but more pronounced in the latter, and not affected by IL-2/IL-2R treatment alone, suggesting IL-2/IL-2R-Treg-mediated modulation of inflammatory response in stroke. Altogether, these observations support the use of IL-2/IL-2R treatment in enhancing the anti-inflammatory effects of Tregs in stroke.

Obesity Drives Delayed Infarct Expansion, Inflammation, and Distinct Gene Networks in a Mouse Stroke Model - Todd C. Peterson; Kendra J. Lechtenberg; Brian D. Piening; Tawaun A. Lucas; Eric Wei; Hassan Chaib; Alexa K. Dowdell; Michael Snyder; Marion S. Buckwalter (Translational Stroke Research, 2021)

Solvent Effects on Skin Penetration and Spatial Distribution of the Hydrophilic Nitroxide Spin Probe PCA Investigated by EPR - Pin Dong; Christian Teutloff; Jürgen Lademann; Alexa Patzelt; Monika Schäfer-Korting; Martina C. Meinke (Cell Biochemistry and Biophysics, 2020)
Oxidative stress occurs in extrinsic skin aging processes and diseases when the enhanced production of free radicals exceeds the homeostatic antioxidant capacity of the skin. The spin probe, 3-(carboxy)-2,2,5,5-tetramethylpyrrolidin-1-oxyl (PCA), is frequently used to study the cutaneous radical production by electron paramagnetic resonance (EPR) spectroscopy. This approach requires delivering PCA into the skin, yet solvent effects on the skin penetration and spatial distribution of PCA have not been thoroughly investigated. Three solvents of ethanol, phosphate-buffered saline (PBS) and ethanol-PBS (1:1) were studied. For both human and porcine skin ex vivo, the amount of PCA in the stratum corneum (SC) was the lowest when using ethanol and very similar for PBS and ethanol-PBS. The highest amount of PCA in the viable skin layers was detected for ethanol-PBS, yet it only took up less than 5% of the total amount. The majority of PCA was localized in the SC, among which PCA with high mobility was predominantly distributed in the hydrophilic microenvironment of corneocytes and PCA with lower mobility was mainly in the less hydrophilic microenvironment of intercellular skin lipids. A higher ethanol concentration in the solvent could improve the distribution of PCA in the hydrophilic microenvironments of the SC. The results suggest that ethanol-PBS (1:1) is best-suited for delivering most PCA deep into the skin. This work enhances the understanding of solvent effects on the skin penetration and distribution of PCA and supports the utilization of PCA in studying cutaneous radical production.

The chemical convulsant diisopropylfluorophosphate (DFP) causes persistent neuropathology in adult male rats independent of seizure activity - Eduardo A. González; Alexa C. Rindy; Michelle A. Guignet; Jonas J. Calsbeek; Donald A. Bruun; Ashish Dhir; Peter Andrew; Naomi Saito; Douglas J. Rowland; Danielle J. Harvey; Michael A. Rogawski; Pamela J. Lein (Archives of Toxicology, 2020)

Genetic diversity of strawberry mild yellow edge virus from eastern Canada - Yu Xiang; Xianzhou Nie; Mike Bernardy; Jun-jun Liu; Li Su; Basdeo Bhagwat; Virginia Dickison; Janesse Holmes; Jenna M. Grose; Alexa C. Creelman (Archives of Virology, 2020)

mGluR5 Allosteric Modulation Promotes Neurorecovery in a 6-OHDA-Toxicant Model of Parkinson’s Disease - Kyle Farmer; Khaled S. Abd-Elrahman; Alexa Derksen; Elyn M. Rowe; Ashley M. Thompson; Christopher A. Rudyk; Natalie A. Prowse; Zachary Dwyer; Samantha C. Bureau; Teresa Fortin; Stephen S.G. Ferguson; Shawn Hayley (Molecular Neurobiology, 2020)

Occurrence of pathogens in Pacific lamprey (Entosphenus tridentatus) - Aaron D. Jackson; Mary L. Moser; Sam T. Onjukka; Scott LaPatra; Kenneth M. Lujan; Corie Samson; Melissa G. White; Marilyn Blair; Linda Rhodes; Ralph Lampman; Alexa N. Maine; Jeffrey C. Jolley (Reviews in Fish Biology and Fisheries, 2019)

Interleukin 6-Mediated Endothelial Barrier Disturbances Can Be Attenuated by Blockade of the IL6 Receptor Expressed in Brain Microvascular Endothelial Cells - Kinga G. Blecharz-Lang; Josephin Wagner; Alexa Fries; Melina Nieminen-Kelhä; Jörg Rösner; Ulf C. Schneider; Peter Vajkoczy (Translational Stroke Research, 2018)

Eruptive and environmental processes recorded by diatoms in volcanically dispersed lake sediments from the Taupo Volcanic Zone, New Zealand - Margaret A. Harper; Shirley A. Pledger; Euan G. C. Smith; Alexa R. Van Eaton; Colin J. N. Wilson (Journal of Paleolimnology, 2015)

Visitation rate and behavior of urban mesocarnivores differs in the presence of two common anthropogenic food sources - Tad C. Theimer; Anthony C. Clayton; Alexa Martinez; Damon L. Peterson; David L. Bergman (Urban Ecosystems, 2015)

Can nutrients mask community responses to insecticide mixtures? - Alexa C. Alexander; Ana T. Luis; Joseph M. Culp; Donald J. Baird; Allan J. Cessna (Ecotoxicology, 2013)

Single Versus Combined Lethal Effects of Three Agricultural Insecticides on Larvae of the Freshwater Insect Chironomus dilutus - Heidi M. K. LeBlanc; Joseph M. Culp; Donald J. Baird; Alexa C. Alexander; Allan J. Cessna (Archives of Environmental Contamination and Toxicology, 2012)

The cost of incline locomotion in ghost crabs (Ocypode quadrata) of different sizes - Alexa Tullis; Scott C. Andrus (Journal of Comparative Physiology B, 2011)